Maturity onset diabetes of the young and fibrin-related thrombosis risk - Sagar, RC; Phoenix, F; Thanabalasingham, G; Naseem, K; Ajjan, RA; Owen, KR (SAGE Publications, 2020)
Background: Fibrin network characteristics determine predisposition to cardiovascular disease (CVD). Individuals with type 1 (T1DM) and type 2 diabetes mellitus (T2DM) have higher risk of CVD and display deranged fibrin network structure. Those with maturity onset diabetes of the young (MODY) may also be at increased risk but their fibrin clot properties have not been studied. Methods: Plasma clots properties from 13 individuals with HNF1A-MODY, 12 matched-individuals with T2DM and 12 with T1DM were studied using a validated turbidimetric assay and confocal microscopy. Plasma levels of fibrinogen, plasminogen activator inhibitor-1, complement C3 and C-reactive protein were also measured. Results: MODY clot maximum absorbance was 0.37 ± 0.03 AU, similar to T1DM (0.32 ± 0.03 AU; p = 0.26), but lower than T2DM (0.49 ± 0.03 AU; p = 0.02), with confocal microscopy confirming structural differences. Clot lysis time in MODY was similar to T1DM (456 ± 50 and 402 ± 20 s, respectively; p = 0.09) but shorter than T2DM (588 ± 58 s; p = 0.006). Comparing inflammatory/thrombotic proteins in HNF1A-MODY and T2DM, C3 levels were lower in MODY than T2DM (0.58 ± 0.09 and 0.80 ± 0.1 mg/ml, respectively; p < 0.01). Conclusions: HNF1A-MODY fibrin network alterations are at least as pronounced as in T1DM but less thrombotic than T2DM clots. Differences in fibrin clot characteristics comparing HNF1A-MODY and T2DM may, in part, relate to lower C3 levels.